Exploring Algerian EFL Master’s Students’ Attitudes Toward AI-giarism - Ghounane, Nadia; Rahmani, Asma; Al-Zubaidi, Khairi (Indonesian Journal of Social Science Research, 2024)
This paper explores Algerian EFL Master’s students’ attitudes toward using AI Generators like QuillBot and ChatGPT to AI-giarize. The researchers selected 66 Algerian EFL Master’s students from the University of Saida, Dr. Moulay Tahar, Algeria. The study adopted a semi-structured questionnaire and an analysis of three selected Master’s theses. The results indicated that students shared positive attitudes toward AI generators in plagiarising, including QuillBot. The findings also revealed that the students had poor knowledge acknowledging the use of these generators. The results also showed that the students received no guidance from their teachers and supervisors on the advantages of these generators in academic writing and raising their awareness against their use to plagiarize. The study concludes that AI generators harm the Algerian educational system if case institutions and universities do not put regulations and raise teachers’ and students’ awareness toward their use.